Perancangan Aplikasi Distribusi Barang Berbasis Android Di PT Abc - Pangestu, Yoga Triyuli; Firdausi, Muhammad Kahlil (Jurnal Instrumentasi dan Teknologi Informasi (JITI), 2024)
The process of goods transactions carried out at PT ABC is not efficient because in the transaction process the goods requester has to go to the technical department, FI department and ADH to ask for transaction approval in the form of a signature. The purpose of this research is to design a goods distribution application to streamline the transaction process and digitize the goods transaction process. This study uses the Waterfall method in designing goods distribution applications. An application made based on Android with Firebase as a database. The user will make a transaction using an Android cellphone, then the transaction data will enter the database and send a request for approval to the technical department, FI department and ADH. Then the three parties will agree to use a special account. The transaction process has been successfully digitized through the application so that users can connect with the goods distribution application.